Effectiveness of N95 Masks against SARS-CoV-2: Performance Efficiency, Concerns, and Future Directions - Rashid, Taslim Ur; Sharmeen, Sadia; Biswas, Shanta (ACS Chemical Health & Safety., 2022)
The coronavirus disease 2019 (COVID-19) epidemic, which is caused by novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has continued to spread around the world since December 2019. Healthcare workers and other medical first responders in particular need personal protective equipment to protect their respiratory system from airborne particulates, in addition to liquid splashes to the face. N95 respirator have become a critical component for reducing SARS-CoV-2 transmission and controlling the scale of the COVID-19 pandemic. However, a major dispute concerning the protective performance of N95 respirators has erupted, with a myriad of healthcare workers affected despite wearing N95 masks. This article reviews the most recent updates about the performance of N95 respirators in protecting against the SARS-CoV-2 virus in the present pandemic situation. A brief overview of the manufacturing methods, air filtration mechanisms, stability, and reusability of the mask is provided. A detailed performance evaluation of the mask is studied from an engineering point of view. This Review also reports on a comparative study about the protective performance of all commercially available surgical and respiratory masks used to combat the spread of COVID-19. With the aim of protecting healthcare providers more efficiently, we suggest some potential directions for the development of this respiratory mask that improve the performance efficiency of the mask.